Quand l'État appauvrit les femmes. Réalités de travailleuses de soins à domicile francophones au Nouveau-Brunswick - Albert, Hélène; Savoie, Lise; Lanteigne, Isabel; Savoie, Elda; Hinse, Elyse (Revue canadienne de service social, 2019)
Résumé Cet article présente des résultats d’une recherche qualitative portant sur la fragilité des conditions symboliques et matérielles dans lesquelles le travail de soins à domicile se déploie au Nouveau-Brunswick. Dans cette province, l’État, dans le développement de politiques sociales en matière de santé et de services sociaux, souhaite que le secteur des soins à domicile devienne la pierre angulaire de son système de santé dans une volonté de maintenir des personnes âgées à demeurer à domicile le plus longtemps possible. Ce faisant le modèle de livraison de service développé repose sur une organisation qui implique l’embauche de travailleuses de soins à domicile devenant ainsi un secteur d’activités qui se caractérise par une surreprésentation féminine de la main-d’oeuvre. Au Nouveau-Brunswick, les femmes qui oeuvrent dans ce secteur sont soumises à des conditions de travail précaires qui les maintiennent dans la pauvreté. Les résultats révèlent ainsi que la précarité de ces travailleuses est accentuée par les conditions matérielles difficiles. En effet, le salaire, l’horaire de travail, les avantages sociaux, les dépenses ou les frais afférents à leur travail sont au nombre de ces conditions qui les maintiennent dans des conditions précaires. Pourtant, ces femmes jouent un rôle essentiel dans notre société, elles qui, par leur travail du care, assument des responsabilités professionnelles fondamentales au maintien du lien social. C’est donc tout un système qui est complice de l’appauvrissement de ces femmes, tout un système qui n’offre à ces dernières, ni la reconnaissance matérielle, ni la reconnaissance symbolique de leur contribution. Mots-clés : Pauvreté, femmes, soins à domicile, care, travailleuses pauvres, non reconnaissance Abstract This article presents the results of a qualitative research focusing on the fragility of the symbolic and material home health care work conditions in New Brunswick. In the context of health care and social service policy development in the province, the government wishes to establish the home health care sector as the cornerstone of the province’s health care system with a view to keeping seniors at home as long as possible. In so doing, the service delivery model developed involves hiring home caregivers, thus creating female overrepresentation in this activity sector. In New Brunswick, women working in this sector are subject to precarious working conditions that keep them in poverty. Findings reveal that women workers’ insecurity is exacerbated by difficult material conditions. Pay, work schedule, social benefits, and work-related expenses and costs are among the factors perpetuating their precarious condition. And yet, these women play a crucial role in society inasmuch as through the caregiving service that they provide, they assume professional responsibilities that are essential to maintaining social bonds. Consequently, an entire system is complicit in these women’s impoverishment, an entire system withholds the material and symbolic recognition of their contribution. Keywords: Poverty, women, home care, care, poor women workers, non-recogniti

Recruiting doctors from and for underserved groups: Does New Brunswick's initiative to recruit doctors for its linguistic minority help rural communities? - Beauchamp, Jacinthe; Bélanger, Mathieu; Schofield, Aurel; Bordage, Rachel; Donovan, Denise; Landry, Michel (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objectives Within health care, there are underserved groups. New Brunswick’s French-speaking minority, which also mostly lives in rural communities, is one such group. A physician shortage potentially prevents this population from accessing health promotion and clinical prevention services. This study analyzes whether New Brunswick Francophone doctors with rural backgrounds are more likely than doctors from urban regions to set up practice in rural communities of the province. Methods A questionnaire was sent to 390 New Brunswick Francophone physicians admitted in medicine between 1973 and 2000. It collected information on geographic origin and history of medical practice. Multivariate logistic regressions were used to identify whether a rural background is associated with the likelihood of ever and currently practicing in rural communities. We used the General Practice Rurality Index-simplified to quantify the rurality level of communities. Results In total, 264 (67%) physicians participated. A rural background was positively associated with the establishment of a first medical practice in a rural community. This relationship was only significant among family physicians. There was no statistically significant relationship between rurality of community of origin and rurality of current community of practice among either family or specialty physicians. Conclusion Although Francophone doctors with a rural background were more likely than their urban counterparts to set up their first practice in a rural community, this effect was not sustained. This raises questions as to why they leave rural communities and highlights the importance of measures to retain doctors as a way to promote public health for underserved rural groups.

L’attraction organisationnelle et les valeurs des jeunes : le cas du personnel infirmier en milieu hospitalier - Bouchard, Pier; Vézina, Sylvain (Minorités linguistiques et société, 2015)
La prestation de services de santé de qualité aux communautés francophones soulève la question de la disponibilité des ressources humaines, des jeunes professionnels en particulier. Ainsi, les gestionnaires des établissements de santé doivent élaborer des stratégies de recrutement/rétention qui tiennent compte des aspirations et des valeurs des jeunes. À cet égard, nous présentons ici les résultats d’une enquête menée auprès d’infirmières et de gestionnaires d’un important établissement de santé francophone du Nouveau-Brunswick. Ces résultats nous amènent à proposer des pistes d’action susceptibles de favoriser l’engagement des jeunes professionnels qui deviendront les ambassadeurs de services de santé en français de qualité. Mots-clés : services de santé en français, valeurs et aspirations des jeunes, recrutement, rétention, infirmières, gestion des ressources humaines, hôpital, leadership transformationnel

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.
Chapitre 7

L’offre de services de santé en français en contexte francophone minoritaire - Forgues, Éric; Bahi, Boniface; Michaud, Jacques; Deveau, Kenneth; Boudreau, Jonathan; St-Onge, Sylvain (Institut canadien de recherche sur les minorités linguistiques, 2011)

La reconnaissance des diplômés internationaux francophones en santé : un potentiel pour les communautés francophones en situation minoritaire au Canada - Lafontant, Jean; Forgues, Éric; Belkhodja, Chedly; Sangwa-Lugoma, Ghislain; Meridji, Tayeb; Pietrantonio, Linda; Tremblay, André; Kayirangwa, Christine (Institut canadien de recherche sur les minorités linguistiques, 2006)

Préparer le terrain : soins et services de santé primaires en français au Nouveau-Brunswick - Société Santé et Mieux-être en français du Nouveau Brunswick (Préparer le terrain : soins et services de santé primaires en français au Nouveau-Brunswick)